Synthesis and Biological Evaluation of 2,5-Bis(alkylamino)-1,4-benzoquinones - Cláudia Pessoa; Manoel Odorico Moraes; Letícia Veras Costa-Lotufo; José Roberto Oliveira Ferreira; Vânia Maria Moreira Valente; Róbson Ricardo Teixeira; Célia Regina Alvares Maltha; Ulisses Alves Pereira; Luiz Cláudio Almeida Barbosa (Molecules, 2010)
A series of twelve 2,5-bis(alkylamino)-1,4-benzoquinones were prepared in yields ranging from 9–58% via the reaction between p-benzoquinone and various amines. The structures of the synthesized compounds were confirmed by IR, 1H- and 13C-NMR and MS analyses. The phytotoxicity of the 2,5-bis(alkylamino)-1,4-benzoquinones was evaluated against two crop species, Cucumis sativus and Sorgum bicolor, at 1.0 × 10-3 mol/L. In general, the quinones displayed inhibitory effects on the dicotyledonous species C. sativus (7–74%). On the other hand stimulatory effects were observed on S. bicolor (monocotyledonous). Similar results were observed in the biological assays carried out with the weed species Ipomoea grandifolia (dicotyledonous) and Brachiaria decumbens (monocotyledonous). In addition, the cytotoxicity of the 2,5-bis(alkylamino)-1,4-benzoquinones was assayed against HL-60 (leukemia), MDA-MB-435 (melanoma), SF-295 (brain) and HCT-8 (colon) human cancer cell lines and human peripheral blood mononuclear cells (PBMC), as representatives of healthy cells, using a MTT and an Alamar Blue assay. Compound 12 was the most active, displaying cytotoxicity against all cancer cell lines tested.